HUBUNGAN SELF EFFICACY DENGAN KECEMASAN PENDERITA GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RSUD JOMBANG - Uswatun hasanah; Heni Maryati; Pepin Nahariani (Universitas Nahdlatul Ulama Surabaya, 2017)
Chronic kidney disease is irreversible, meaning there could be normal again, who could do is maintain existing renal function undergoing dialysis treatment throughout their lives (usually 1-3 times a week) or to get a new kidney through a kidney transplant operation. It can lead to psychological disorders such as anxiety. With Anxiety will exacerbate the perceived disease. One of the factors that influence anxiety is self-efficacy. This research aims to determine the correlation of self-efficacy with the level of anxiety in patients with chronic renal failure undergoing hemodialysis in Jombang Public Hospitals.This research is a correlation analytic method with cross sectional approach. In this research population of 33 respondents include all patients with chronic renal failure undergoing hemodialysis in Jombang Public Hospitals first time - 6 months. A sample of 30 respondents were taken using accidental sampling. The independent variable was self-efficacy, the dependent variable anxiety, how to collect data by statistical tests used questioner Spearman's rank. The research was conducted on 24-31 May 2016. The statistical test used in this study was Spearman's rank correlation. Based on the results of research in Hemodialysis room Jombang Public Hospitals found that half (50%) of respondents have a positive self-efficacy and nearly half (36.7%) of respondents are not anxiety. Statistical test results showed significancy value of 0.001(p <0.05). It was indicated that there was a correlation of self-efficacy with the level of anxiety in patients with chronic renal failure undergoing hemodialysis in the hemodialysis room Jombang Public Hospitals in 2016.Need to improve services through counseling, information and education on management of chronic renal failure and can provide knowledge about self efficacy other than that can involve the family in supporting the implementation of self-efficacy.